PENGEMBANGAN PERANGKAT AJAR BERBASIS CTL PADA MATERI SISTEM KOORDINAT UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH KELAS VIII - Azizah, Tuti; Sepriyanti, Nana; Eliza, Rivdya (UIN Imam Bonjol Padang, 2023)
The purpose of the research is to produce Student Worksheet based on Contextual Teaching and Learning (CTL) on the coordinate system material that meets the valid, practical, and effective criteria. This type of research is the research and development of Research and Development (RD) with the ADDIE model proposed by Dick and Carry (1998), which consists of five stages of development namely Analysis, Design, Develop, Implementation, and Evaluation. The subjects in this study were 3 educators and 12 students of class VIII of SMPN 8 Payakumbuh. Data analysis technique was done by analyzing the validity and practicality assessment sheets of the use of CTL-based LKPD. The results showed that the use of CTL-based LKPD developed obtained an average score of 84.66% which included very valid criteria. Furthermore, based on the practicality test showed that the revised CTL-based LKPD received an average score of 86.88% which was included in the very practical criteria. Finally, based on the effectiveness test showed that the CTL-based LKPD that was developed to improve students' problem solving abilities based on the acquisition of the average value of the problem solving ability test which was 86, 25% above the KKM. It was concluded that CTL-based LKPD in mathematics learning on the coordinate system material developed had fulfilled valid, practical, and effective criteria.